Sufism and the Idrisiyyah Order: An Approach to Religious Moderation in Contemporary Islam - mursalat, Mursalat; Siswoyo Aris M (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2024)
This article discusses the role of Sufism, particularly the Idrisiyyah Order, in promoting religious moderation in the contemporary Islamic era. This research employs a library research method, collecting and analyzing written sources from books, scholarly journals, articles, and official documents. The data collected includes literature on Sufism, the Idrisiyyah Order, and religious moderation in contemporary Islam. The approach combines sociological and religious perspectives, aiming to understand how the Idrisiyyah Order contributes to modern society and how Sufi teachings and the values of religious moderation are applied in daily life. Using the literature study method, this research explores how the teachings of the Idrisiyyah Order, founded by Ahmad Ibnu Idris al-Fasi, emphasize the principles of love, tolerance, and spirituality. This order emerged as a response to the radicalism and extremism prevalent in today's society. The Idrisiyyah Order is crucial in shaping moderate attitudes through educational approaches, community economic development, and strengthening social networks in Indonesia. These Sufi teachings focus on purifying the heart and spreading compassion, contributing to rejecting violence and intolerance. In this way, the Idrisiyyah Order helps create a more harmonious and peaceful society, demonstrating that spiritual teachings can significantly address contemporary social challenges. This study provides insight into how spiritual approaches can effectively promote moderation and tolerance in Islam